Targeting Adipokines in Obesity-Related Tumors - Pu, Xi; Chen, Deyu (Frontiers in Oncology, 2021)
Obesity, a global epidemic, is an independent risk factor for the occurrence and development of a variety of tumorigenesis, such as breast cancer, pancreatic cancer, ovarian cancer and colorectal cancer. Adipocytes are important endocrine cells in the tumor microenvironment of obesity-related tumors, which can secrete a variety of adipokines (such as leptin, adiponectin, estrogen, resistin, MIF and MCP-1, etc.), among which leptin, adiponectin and estrogen are the most in-depth and valuable ones. These adipokines are closely related to tumorigenesis and the progression of tumours. In recent years, more and more studies have shown that under chronic inflammatory conditions such as obesity, adipocytes secrete more adipokines to promote the tumorigenesis and development of tumors. However, it is worth noting that although adiponectin is also secreted by adipocytes, it has an anti-tumor effect, and can cross-talk with other adipokines (such as leptin and estrogen) and insulin to play an anti-tumor effect together. In addition, obesity is the main cause of insulin resistance, which can lead to the increase of the expression levels of insulin and insulin-like growth factor (IGF). As important regulators of blood glucose and lipid metabolism, insulin and IGF also play an important role in the progress of obesity related tumors. In view of the important role of adipokines secreted by adipocytes and insulin / IGF in tumors, this article not only elaborates leptin, adiponectin and estrogen secreted by adipocytes and their mechanism of action in the development of obesity- related tumors, but also introduces the relationship between insulin/IGF, a regulator of lipid metabolism, and obesity related tumors. At the same time, it briefly describes the cancer-promoting mechanism of resistin, MIF and MCP-1 in obesity-related tumors, and finally summarizes the specific treatment opinions and measures for various adipokines and insulin/insulin-like growth factors in recent years.